Welfare cost of business cycles with idiosyncratic consumption risk and a preference for robustness - Ellison, M; Sargent, TJ (American Economic Association, 2015)
The welfare cost of random consumption fluctuations is known from De Santis (2007) to be increasing in the level of uninsured idiosyncratic consumption risk. It is known from Barillas, Hansen, and Sargent (2009) to increase if agents care about robustness to model misspecification. We calculate the cost of business cycles in an economy where agents face idiosyncratic consumption risk and fear model misspecification, finding that idiosyncratic risk has a greater impact on the cost of business cycles if agents already fear model misspecification. Correspondingly, endowing agents with fears about misspecification is more costly when there is already idiosyncratic risk.